Implementasi Strategi Pembelajaran Aktif Berbasis Partisipatif dalam Meningkatkan Keterlibatan Belajar Siswa di Sekolah - Umul Nazira; Anisa Masyitoh; Gusmaneli . (CV. ITTC INDONESIA, 2026)
This study aims to analyze the implementation of participatory-based active learning strategies in improving student engagement in schools. The background of this research is based on the low level of student participation in the learning process, which tends to be passive and teacher-centered. The research method used is a qualitative approach with a descriptive design. The research subjects include teachers and students in a secondary school. Data collection techniques were carried out through observation, interviews, and documentation. The results of the study indicate that the implementation of participatory-based active learning strategies, such as group discussions, interactive questioning, and project-based learning, can significantly enhance student engagement. Students become more active in asking questions, expressing opinions, and collaborating in groups. In addition, this strategy also has a positive impact on students’ motivation and understanding of the learning material. In conclusion, the implementation of participatory-based active learning strategies is effective in creating a more dynamic learning environment and improving student engagement in schools. Therefore, teachers are encouraged to optimize the use of this strategy in the learning process.